VULNERABILITY LEVEL MAP OF TSUNAMI DISASTER IN PANGANDARAN BEACH, WEST JAVA - Iqoh Faiqoh; Jason Lumban Gaol; Marisa Mei Ling (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2013)
Indonesia is located in a seismic active region where tsunami often occur. One of tsunami prone areas in Indonesia is southern coast of Java, such as the coastal areas of Pangandaran, West Java. One of the instruments in the tsunami disaster mitigation is the vulnerability map of coastal region on tsunami. Analyses of tsunami vulnerability assessment was performed by using merger or overlay methods in Geographic Information Systems (GIS). The parameters used to analyze tsunami vulnerability level were elevation, topography, landuse, coastal border, and river banks. The vulnerability were divided into five classes i.e., very high, high, medium, low, and very low. Results showed that Pananjung, Babakan, Pangandaran (Pangandaran District); and Sukaresik and Cikembulan (Sidamulih District) sub-districts were identified as areas of very high level of tsunami vulnerability with total area of 737.703 hectares. Areas with low level of vulnerability were Pagergunung, Putrapinggan, and Kersaratu sub-districts with total area of 4,816.204 hectares.